Seismic Anisotropy of Temperate Ice in Polar Ice Sheets. Issue 11 (30th October 2020) - Llorens, M.‐G.; Griera, A.; Bons, P. D.; Gomez‐Rivas, E.; Weikusat, I.; Prior, D. J.; Kerch, J.; Lebensohn, R. A.
Abstract: We present a series of simple shear numerical simulations of dynamic recrystallization of two‐phase nonlinear viscous materials that represent temperate ice. First, we investigate the effect of the presence of water on the resulting microstructures and, second, how water influences on P wave ( V p ) and fast S wave ( V s ) velocities. Regardless the water percentage, all simulations evolve from a random fabric to a vertical single maximum. For a purely solid aggregate, the highest V p quickly aligns with the maximum c ‐axis orientation. At the same time, the maximum c ‐axis development reduces V s in this orientation. When water is present, the developed maximum c ‐axis orientation is less intense, which results in lower V p and V s . At high percentage of water, V p does not align with the maximum c ‐axis orientation. If the bulk modulus of ice is assumed for the water phase (i.e., implying that water is at high pressure), we find a remarkable decrease of V s while V p remains close to the value for purely solid ice. These results suggest that the decrease in V s observed at the base of the ice sheets could be explained by the presence of water at elevated pressure, which would reside in isolated pockets at grain triple junctions. Under these conditions water would not favor sliding between ice grains. However, if we consider that deformation dominates over recrystallization, water pockets get continuously stretched, allowing water films to be located at grain boundaries. This configuration would modify and even overprint the maximum c ‐axis‐dependent orientation and the magnitude of seismic anisotropy. Key Points: Through numerical simulations we analyze the velocities of seismic P and S waves in temperate ice undergoing dynamic recrystallization The highest V p aligns with the maximum c ‐axis orientation in pure ice samples, while it does not align when enough water is present If water is at high pressure, at the ice‐sheet base, the reduction of the S wave velocity is remarkably stronger than that of the P wave